Features power ectomorphs athletes are engaged in bodybuilding in transition training - Джим Віктор Юрійович (Viktor Dzhym) (Slobozhanskyi Herald of Science and Sport, 2015)
Purpose: to develop and study the diet of athletes engaged in bodybuilding ectomorphs in transition training considering the restoration of lean body mass and functional state of an athlete Material and Methods: the study involved 18 athletes engaged in bodybuilding ectomorphs included in the national team in the Kharkiv region bodybuilding. Methods were used: the theoretical method and summarize the literature, pedagogical supervision, pedagogical experiment, methods of mathematical statistics. Results: comparative characteristics of the diet have been developed for athletes ectomorphs engaged on bodybuilding to increase muscle weight. It was divided the athletes into two experimental groups: the first EG used a balanced diet that made protein 2 grams per 1 kilogram of body weight and carbohydrates 4–5 g·kg–1 in the second EG was protein 3 grams per 1 kilogram of body weight, and carbohydrate 6 grams kg. Second EG diet consists of 6 single meal and is about 2800–3500 calories per day. Conclusions: on the basis of research by the author offered the optimal diet for athletes ektomorfiv second experimental group engaged in bodybuilding.